Treatment of acute apical periodontitis using a modified 3Mix paste in a patient with congenital cytomegalovirus infection. Case report - Sucapuca Vilca, Vilma Edith (2021)
Congenital cytomegalovirus is a double-stranded DNA virus belonging to the Herpesviridae family that causes intrauterine infection. Infants can be either asymptomatic or symptomatic at birth. Severe outcome was defined as: neonatal death and/or severe neurodevelopmental symptoms and/or severe cognitive impairment. This study aims at showing the antimicrobial effect of the modified 3-mix paste in the treatment of acute apical periodontitis in a female child patient with congenital cytomegalovirus, in a single session. The 2-year and 3-month-old female patient has symptomatic congenital cytomegalovirus infection and ongoing long-term side effects. At the stemmatological level, the patient presented with multiple carious lesions, reversible pulpitis and acute apical periodontitis. Also, pulpectomies were performed on teeth 61, 62, 51, 52, 81, 71, 54 and 64 in a single session, under general anesthesia. In the pulpectomy of tooth 61, the intracanal obturation material was applied with a modified (with a composition of ciprofloxacin, metronidazole and cephalexin) 3Mix paste, using macrogol and propylene glycol as vehicles in the apical third of the tooth, and oxide zinc and eugenol in the middle and cervical third of the tooth. It was decided that the reconstruction of the tooth would be performed with fiberglass posts and resin restorations based on addition silicone impressions. Conclusion: At 30 days and 6 months after treatment, the patient shows no evidence of pain, swelling/abscess or fistula, and there is no sign of pathologic tooth mobility.